Chapter Vascular Tissue Development and Regeneration in the Model Plant Arabidopsis - Mazur, Ewa (InTechOpen, 2017)
Development of vascular tissue is a remarkable example of intercellular communication and coordinated development involving hormonal signaling and tissue polarity. Thus far, studies on vascular patterning and regeneration have been conducted mainly in trees-woody plants-with a well-developed layer of vascular cambium and secondary tissues. Trees are difficult to use as genetic models, i.e., due to long generation time, unstable environmental conditions, and lack of available mutants and transgenic lines. Therefore, the use of the main genetic model plant Arabidopsis thaliana (L.) Heynh., with a wealth of available marker and transgenic lines, provides a unique opportunity to address molecular mechanism of vascular tissue formation and regeneration. With specific treatments, the tiny weed Arabidopsis can serve as a model to understand the growth of mighty trees and interconnect a tree physiology with molecular genetics and cell biology of Arabidopsis.